Test of anthocyanin level and evaluation of rambutan leaf extract (nephelium lappacheum L.) as an alternative to disclosing material of dental plaque detection solution - Asti P. Adnan; Siti Z. Tripalu; Erwin Gunawan; Ahmad S. Jarigau; Rini Pratiwi (Journal of Dentomaxillofacial Science, 2019)
Objective : Data from Rikesdas in 2007, the society has problems of oral health of 23.2 per cent. This is because of the accumulation of the plaque. The most basic efforts to reduce it is detect plaque with the material disclosing solution. However the materials disclosing solution currently uses a variety of chemicals. This aspects influenced researchers to make disclosing materials of natural-based solution can be obtained from the bark of rambutan (Nephelium lappaceum L.) containing anthocyanins that can be used to detect dental plaque.Material and Methods: The subject of research is the male mice are applied topically with rambutan leaf extract solution on the mice teeth. Methods undertaken consisted of testing the determination of the levels of anthocyanin with pH Differensial methods, test the determination of content the total phenolic with method folin-ciocalteu, test the determination of the activity catcher free radical DPPH, and qualitative analysis of flavonoids in order to prove the existence one of flavonoid compounds, namely in the form of anthocyanin compounds. In addition, researcher do toxicity test and detection of the plaque. This is done to know the rambutan leaf extract can be safely used by the public and can be used as dental plaque detection.Result: Rambutan leaf extract has flavonoid compounds in the form of anthocyanin compounds that is safe for the body and can be used as dental plaque detection.Conclusion: The conclution that rambutan leaf based disclosing solution is effective for detecting dental plaque.